2013
DOI: 10.1111/jace.12649
|View full text |Cite
|
Sign up to set email alerts
|

Ba5Li2W3O15: A New Li‐Containing Perovskite‐Type Microwave Ceramic with High Q and Low τf

Abstract: A new Li-containing microwave ceramic Ba 5 Li 2 W 3 O 15 with hexagonal perovskite structure was prepared through a solidstate ceramic route. Small amount of scheelite BaWO 4 appeared as a second phase during sintering. The Ba 5 Li 2 W 3 O 15 could be well densified at 1120°C and exhibits good microwave dielectric properties with permittivity (e r ) of 25.4, high Q 3 f value about 39 000 GHz, and low temperature coefficient of resonate frequency (s f ) of 10 ppm/°C. The addition of BaCu(B 2 O 5 ) can effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Microwave materials are required to have suitable permittivity (ε r ), high quality factor (Q Â f) for better selectivity and near-zero temperature coefficient of resonant frequency (τ f ) for stability, preferably with a low sintering temperature [1][2]. Recently a large number of researchers are paying attention to develop new microwave dielectric ceramics with intrinsic low sintering temperature for application in LTCC [3][4][5], such as WO 3 -based and Li 2 O-based materials [6][7]. In Li 2 O-M 2 O 3 -WO 3 systems, Li 2 WO 4 [8] and double tungstates LiMW 2 O 8 (M ¼Y, Nd, Sm, Bi) [9][10][11][12] were reported to have a low sintering temperature (650-900°C), but a large negative τ f value of À146 ppm/°C for Li 2 WO 4 and a positive value (þ 63.8 ppm/°C $ þ142 ppm/°C) for M ¼Y, Nd, Sm.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave materials are required to have suitable permittivity (ε r ), high quality factor (Q Â f) for better selectivity and near-zero temperature coefficient of resonant frequency (τ f ) for stability, preferably with a low sintering temperature [1][2]. Recently a large number of researchers are paying attention to develop new microwave dielectric ceramics with intrinsic low sintering temperature for application in LTCC [3][4][5], such as WO 3 -based and Li 2 O-based materials [6][7]. In Li 2 O-M 2 O 3 -WO 3 systems, Li 2 WO 4 [8] and double tungstates LiMW 2 O 8 (M ¼Y, Nd, Sm, Bi) [9][10][11][12] were reported to have a low sintering temperature (650-900°C), but a large negative τ f value of À146 ppm/°C for Li 2 WO 4 and a positive value (þ 63.8 ppm/°C $ þ142 ppm/°C) for M ¼Y, Nd, Sm.…”
Section: Introductionmentioning
confidence: 99%
“…To use BNO ceramics in type I ceramic multilayer applications, it is important to understand the dielectric response over a broad range of measurement frequency. It was found that some hexagonal perovskite oxides have been found to be the candidate materials for dielectric resonators in the base station of telecommunication systems . Among the hexagonal perovskites, Ba 5 Nb 4 O 15 (BNO) ceramics are promising due to its excellent dielectric properties in bulk form: high dielectric constant (ε r ) ~ 39, quality factor ( Q × f 0 ) ~ 26.3 THz, and temperature coefficient of resonance frequency (τ f ~ +79 ppm/°C), and were first investigated by Galasso and Katz .…”
Section: Introductionmentioning
confidence: 99%
“…To use the most common electrode silver, the ceramic must have low sintering temperature below 960°C and chemical compatibility with Ag . Generally, most of the commercial dielectric materials have a high quality factor and high relative permittivity, but their high sintering temperatures (≥1400°C) would restrict their applications in LTCC devices . Therefore, the search for new microwave dielectric materials with favorable properties and intrinsic low sintering temperatures is in the rapid progress, and a great number of Lithium‐based binary or ternary compounds have been developed as low‐firing microwave dielectric ceramics such as Li 2 TiO 3 , Li 3 NbO 4 , LiZnNbO 4 , and Li 2 O–Nb 2 O 5 –TiO 2 system …”
Section: Introductionmentioning
confidence: 99%